Serum alpha 1-acid glycoprotein, sialic acid, and protein binding of disopyramide in normal subjects and cardiac patients - Chu Jian-She; Kishion Satoshi; Nomura Akikazu; Miyazaki Katsumi (Acta Pharmacologica Sinica, 2016)
AIM: To study influence of congestive heart failure (CHF) and acute myocardial infarction (AMI) on alpha 1-acid glycoprotein (AGP) and sialic acid (SA) concentration, and binding of AGP to disopyramide (Dis). METHODS: Sera from 85 healthy subjects, 6 patients with CHF, and 6 patients with AMI were determined by immunochemistry for AGP, by HPLC method for sialic acid (SA), and by ultrafiltration and HPLC for the free fraction of Dis. RESULTS: Serum AGP concentrations (g.L-1) were 0.74 +/- 0.16 (healthy), 1.18 +/- 0.40 (d 1, CHF) and 0.90 +/- 0.24 (d 14, CHF), 1.53 +/- 0.26 (d 5, AMI) and 1.08 (d 14, AMI). The free Dis were 1.76 +/- 0.62 (d 1) and 2.14 +/- 0.48 (d 14), in CHF patients, 1.66 +/- 0.52 (d 5) and 1.77 (d 14) in AMI patients. The changes of serum SA and AGP concentrations showed the same tendency. CONCLUSION: The free Dis in serum was affected by the change of AGP binding in CHF and AMI patients.